2014
DOI: 10.1021/jz502186a
|View full text |Cite
|
Sign up to set email alerts
|

Ion-Solvation-Induced Molecular Reorganization in Liquid Water Probed by Resonant Inelastic Soft X-ray Scattering

Abstract: The molecular structure of liquid water is susceptible to changes upon admixture of salts due to ionic solvation, which provides the basis of many chemical and biochemical processes. Here we demonstrate how the local electronic structure of aqueous potassium chloride (KCl) solutions can be studied by resonant inelastic soft X-ray scattering (RIXS) to monitor the effects of the ion solvation on the hydrogen-bond (HB) network of liquid water. Significant changes in the oxygen K-edge emission spectra are observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
61
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(69 citation statements)
references
References 42 publications
8
61
0
Order By: Relevance
“…Since changes seem to be dependent on the concentration, it indicates a local impact of Na + . This finding is in agreement with recent results [5,16,33,34]. It is intriguing that the oxygens from CH 3 COO − ions don't contribute to the XE signal significantly see Figure 3.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Since changes seem to be dependent on the concentration, it indicates a local impact of Na + . This finding is in agreement with recent results [5,16,33,34]. It is intriguing that the oxygens from CH 3 COO − ions don't contribute to the XE signal significantly see Figure 3.…”
Section: Resultssupporting
confidence: 93%
“…For the 1 and 2 M spectra, a residue is introduced as a difference between the measured data and the two component fit. It has been proposed that the residue can be interpreted as being the signal from the water molecules in the first solvation shell of the salt ion [16]. Yet, the residues are not significant, which could be due to insufficient signal from water molecules in the first solvation shell.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that the shape of the O K edge NEXAFS spectrum of water changes with the addition of salts, with changes progressing as the salt concentration increases. 49,50 Similar changes are also observed in vibrational sum-frequency spectroscopy. 51 These changes are interpreted as iodine anions (which show a propensity for the interface) 52 weakening the water bonding coordination network near the surface region.…”
Section: Discussionsupporting
confidence: 71%
“…X-ray spectroscopy allows measuring directly the electronic properties of a system and provides direct information about the local electronic structure around a specific element in a bulk chemical environment. [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] Previous soft X-ray absorption studies on aqueous solutions reported strong distortions of the pre-, main-and post edge of the X-ray absorption spectra on the oxygen K-edge in the vicinity of the ions. 7,30,31,33 These changes have been assigned to weakening and strengthening of the hydrogen bonds in the solvation shell around the cations.…”
Section: Tocmentioning
confidence: 99%